HUBUNGAN ASUPAN NATRIUM, KALIUM, DAN AKTIVITAS FISIK DENGAN TEKANAN DARAH PADA PRA LANSIA DAN LANSIA WANITA DI MAJELIS TAKLIM AL-KIROMIYAH KOTA JAKARTA TIMUR PADA MASA PANDEMI COVID-19 - Salsabila Putri Alliansyah (2021)
Blood pressure is the pressure needed to circulate blood throughout the body via blood vessels. Increasing the age of a person is more at risk of increasing blood pressure. In 2018, the City of East Jakarta had a prevalence of hypertension sufferers of 35.45%. The purpose of this study is to determine the relationship between sodium intake, potassium, and physical activity with blood pressure in pre-elderly and elderly women in the Al-Kiromiyah Assembly of East Jakarta City during the COVID-19 pandemic period. This study was an observational analytic study with a cross sectional design. The sample of this study is around 82 respondents using simple random sampling. Data analysis uses the chi-square statistical test. The results of bivariate data analysis showed that there was a relationship between sodium intake (p = 0,000) and physical activity (p = 0,003) with blood pressure in pre-elderly and elderly women. Meanwhile, potassium intake (p = 0,174) did not show a relationship with blood pressure in pre-elderly and elderly women.